Theoretical Study of Positive and Negative Parity Coulomb Transitions in 40,48Ca - Dhhewy, Mohammed M.; Ridha, Arkan R. (Iraqi Journal of Science, 2026)
Hsieh-Wildenthal (HW) and G-matrix PF1, (GXPF1) interactions for 40Ca and 48Ca, respectively. The 40Ca was considered to be consisted of 32S as a core and 1d3/21f7/2 subshells as a model space. The 48Ca was considered to be consisted of 40Ca as a core and 1f7/22p3/21f5/2 2p1/2 subshells as a model space. The obtained one body-density matrix elements (OBDME) for both interactions for the studied Coulomb transitions:  For 40Ca, the three non-normal parity transitions (C3): ,  and  and one C5 transitions,  .  For 48Ca, the two C2 transitions:  and  and one C4 transitions  were used in parallel with the transformed harmonic-oscillator basis to compute charge density, elastic electron scattering differential cross-section and elastic and inelastic Coulomb form factors. Finally, the Bohr-Mottelson (B-M), Tassie (T), and valence (V) models were included in the theoretical calculations for the computed inelastic coulomb form factors.